Adsorption of hexavelent chromium, Cr (VI) by using leucaena leucocephala pods: article - Hamidon, Muhammad Hazim; Abdul Razak, Noor Harliza (2019)
Industrialization and urbanization were the most factors of large amount of heavy metals and other pollutants presents in the wastewater. One of the heavy metals that presents in the wastewater is hexavalent chromium Cr (VI). The present studies have been done by using Leucaena Leucocephala Pods (LLP) as adsorbent in the removal of heavy metals present in the waste water. In the experiment, LL was used in the removal of hexavalent chromium Cr (VI) ions. Thermo Gravimetric Analysis (TGA), Point of zero charge (pHpzc) and Fourier Transform Infrared Spectroscopy (FTIR) were used to characterise the pods of LL. The experimental adsorption parameters investigated include effect of pH, adsorbent dosage and contact time. The best condition of parameters such as 0.25 g of LLP dosage, time of contact of 120 min, pH of 2 indicated the maximum Cr (VI) uptake. This study shows that LLP is an efficient and cost-effective adsorbent for removing Cr (VI) and it can be a solution for Cr (VI) discharging industries.